SEISMIC DATA ON RESIDUAL DISPLACEMENTS IN EXPLOSIONS AND EARTHQUAKES - Grayzer V.M. (My University, 1989)
Traditional instrumental seismologic observations provide information on the accelerations, velocities and displacements of the ground at various distances from the centers of earthquakes and explosions. Seismic instruments can measure the movement of the ground over a limited range of frequencies. The greatest distortions of the measured displacement occur in the low-frequency region. In most cases the residual displacements are not considered by seismologists, and most information on them is obtained from geodetic observations. Geodetic measurements are rarely capable of describing the residual displacements produced by the earthquake process itself. A method of determining the 'true' ground movement from seismic traces, which could be used to reconstruct both oscillatory and residual displacements, was suggested by authors previously. In contrast to geodetic methods, this technique can identify the comparatively rapidly generated residual displacements, produced during seismic tremors intervals of a second. In the present paper the authors identify possible relationships between residual displacements and various characteristics of seismic-wave sources, vibrational intensities, and distance.